eCM 2010
DOI: 10.22203/ecm.v020a35
|View full text |Cite
|
Sign up to set email alerts
|

In vivo local co-delivery of recombinant human bone morphogenetic protein-7 and pamidronate via poly-D, L-lactic acid

Abstract: The effects of bone anabolic agents such as bone morphogenetic proteins (BMPs) have the potential to be augmented by co-treatment with an anti-catabolic such as a bisphosphonate. We hypothesised that the effects of bisphosphonates on BMP-induced bone anabolism would be dose dependent, and we aimed to test this in a small animal model. Agents were delivered locally using a biodegradable poly-D, L-lactic-acid (PDLLA) polymer delivery system. Recombinant human BMP-7 (25 μg) was tested with a range of doses of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…Alternatively, combinations with VEGF or TGF-β3 (Ripamonti et al, 2010) constitute mutualistic approaches where the angiogenic factor induces vessel ingrowth into the defect (2 fold (Zhang et al, 2010a)), the chondrogenic factor induces cartilaginous matrix production to fill the defect void, and the osteogenic factor induces resultant callus mineralisation and eventual bone formation (three lineages important for recapitulation of the in vivo bone healing cascade). Other factors and compounds used in combination with BMP-7 include BBP , FGF-2 , insulin-like growth factor 1 (IGF-1) , pamidronate (Yu et al, 2010a), PDGF (Zhang et al, 2012a), PTH (1-34) (Morgan et al, 2008), TGF-β1 (Ripamonti et al, 2001b) and thrombospondin 1 (TSP-1) (Gelse et al, 2011). Taken together these combinations have demonstrated increased defect regeneration from 1.4 to 5.3 fold in large animals (Ripamonti et al, 2010;Zhang et al, 2009b), and 1.2 to 15 fold in small animals Zhang et al, 2012a).…”
Section: Combination Administration Of Bmp-7mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, combinations with VEGF or TGF-β3 (Ripamonti et al, 2010) constitute mutualistic approaches where the angiogenic factor induces vessel ingrowth into the defect (2 fold (Zhang et al, 2010a)), the chondrogenic factor induces cartilaginous matrix production to fill the defect void, and the osteogenic factor induces resultant callus mineralisation and eventual bone formation (three lineages important for recapitulation of the in vivo bone healing cascade). Other factors and compounds used in combination with BMP-7 include BBP , FGF-2 , insulin-like growth factor 1 (IGF-1) , pamidronate (Yu et al, 2010a), PDGF (Zhang et al, 2012a), PTH (1-34) (Morgan et al, 2008), TGF-β1 (Ripamonti et al, 2001b) and thrombospondin 1 (TSP-1) (Gelse et al, 2011). Taken together these combinations have demonstrated increased defect regeneration from 1.4 to 5.3 fold in large animals (Ripamonti et al, 2010;Zhang et al, 2009b), and 1.2 to 15 fold in small animals Zhang et al, 2012a).…”
Section: Combination Administration Of Bmp-7mentioning
confidence: 99%
“…This may be due to under or over-dosing of one or both of the delivered factors. Consequently, balance between combination choice and dosage should be carefully considered as one study demonstrated a 2-fold decrease in bone formation following high dose pamidronate (2 mg) compared to low dose (20 µg) pamidronate (Yu et al, 2010a). A number of studies have also investigated BMP-7 combinations with cells including BMSCs (Zhang et al, 2011b), MSCs (Tsiridis et al, 2007a) or osteoblasts (Reichert et al, 2011).…”
Section: Combination Administration Of Bmp-7mentioning
confidence: 99%
“…Local and systemic bisphosphonates are reported to reduce TRAP-positive cell numbers (Yu et al, 2010b) and this was also observed in the critical defect model. A group containing both bisphosphonate and HA particles was included as bisphosphonates have an affinity for calcium phosphate.…”
Section: Discussionmentioning
confidence: 61%
“…These challenges associated with resorption can be aggravated by rhBMP treatments, which can promote osteoclastic resorption (Itoh et al, 2001;Kaneko et al, 2000;Pradhan et al, 2006). Thus numerous pre-clinical studies have investigated the efficacy of modulating rhBMP-induced bone formation with adjunct anti-resorptive agents, such as bisphosphonates (Belfrage et al, 2011;Chen et al, 2004;Chen et al, 2006;Jakobsen et al, 2007;Jakobsen et al, 2010;Jeppsson et al, 2003;Yu et al, 2010b;Yu et al, 2013). IKK inhibitors such as PS-1145 also show promise for maximising rhBMP-induced bone formation (Carr et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Poly(D,L-lactic acid) has T g of 55-60 °C and mechanical strength of 1.9 GPa [80]. This polyester requires over a year to properly erode and it is commonly used as drug delivery film [108] and tissue engineering scaffold [109][110][111]. In dentistry, Hile et al investigated the resorption rate of polylactide-based internal fixation devices.…”
Section: Polyestersmentioning
confidence: 99%